The potential gastrointestinal side effects of excipients in imatinib preparations - Akdeniz, Aydan; Orekici, Gulhan; Balik, Berrin; Bakir Koyuncu, Mahmut; Ali Ucar, Mehmet; Tombak, Anil; Tiftik, Nalan; Naci Tiftik, Eyup (Annals of Medical Research, 2021)
Aim: Chronic myeloid leukemia (CML) is a BCR-ABL positive myeloproliferative disorder characterized by clonal proliferation of the hematopoietic stem cells. Imatinib mesylate represents the most important agent associated with improved survival in CML that has been introduced for clinical use in 2000s. The original imatinib preparation Glivec ® was subsequently followed by the introduction of biosimilar products containing a variety of excipients. Gastrointestinal side effects represent the major limitation for therapeutic use of imatinib. This study was planned to examine whether excipients in the original and biosimilar imatinib products had any role in the emergence of GIS side effects. Materials and methods: Excipients in imatinib preparations used for the treatment of chronic phase (CP) CML patients followed up and treated at the hematology department of Mersin University between 2000 and 2019 were analyzed with respect to their potential GIS side effects. Results: Totally 42 CML patients included in the study. The median age was 53.2, and female:male ratio was 20:22. They had similar demographic characteristics as compared to previously reported CML populations. No patients had GIS side effect requiring drug discontinuation or switch to another agent. While bovine gelatin and polyvinyl alcohol had no significant effects on GIS side effects, those that contained titanium were found to be associated with a significant increase in the risk of GIS side effects (52%, contained titanium vs 0/2, contained no titanium). These side effects are less frequently in products that have lowest number of excipient types.Conclusion: GIS side effects can be triggered by various excipients in imatinib preparations
Keywords: Chronic myeloid neoplasm; excipients; gastrointestinal side effects; imatinib; myeloproliferative neoplasm